What happens to ear morphology on the way underground? A case study on the family Spalacidae. - Pleštilová, Lucie (Jihočeská univerzita, 2021)
This PhD thesis is concerned with the effect of specialization to the subterranean environment on ear morphology in the rodent family Spalacidae. The outer, middle and inner ear morphology in four species with a different proportion of subterranean activity was described and analyzed. The Chinese bamboo-rat (Rhizomys sinensis) was identified as fossorial regarding its ear morphology. The strictly subterranean Gansu zokor (Eospalax cansus) possess a highly specialized subterranean ear morphology with a suggested acoustic fovea. Meanwhile, the less subterranean African root-rat (Tachyoryctes splendens) shares traits with both strictly subterranean and epigeic rodents. The aboveground characteristics are even more prominent in the fossorial giant root-rat (T. macrocephalus). Taken together, the results confirm that the ear morphology of spalacids mirrors their degree of fossoriality.
What happens to ear morphology on the way underground? A case study on the family Spalacidae.
Keywords: Ear morphology; middle ear; inner ear; subterranean; fossorial; Spalacidae; muroid mole rats; Chinese bamboo rat; Rhizomys sinensis; Gansu zokor; Eospalax cansus; African roo-rat; Giant root-rat; Tachyoryctes splendens; Tachyoryctes macrocephalus; Ear morphology; middle ear; inner ear; subterranean; fossorial; Spalacidae; muroid mole rats; Chinese bamboo rat; Rhizomys sinensis; Gansu zokor; Eospalax cansus; African roo-rat; Giant root-rat; Tachyoryctes splendens; Tachyoryctes macrocephalus